Pengaruh Tata Kelola, Koneksi Politik, dan Kompensasi Dewan Direksi Terhadap Pengungkapan Tanggung Jawab Sosial - Richo Diana Aviyanti; Heidy Paramitha Devi; Nik Amah; Dwi Nila Andriani; Pramesti Wahyu Widiastuti (Universitas PGRI Madiun, 2022)
Companies must meet public expectations to maintain the social contract. This study aims to determine the effect of corporate governance, political connections, and board of directors compensation on social responsibility disclosure. This study uses a quantitative approach with a positivist paradigm. The population of this study is all issuers of the manufacturing sector listed on the Indonesia Stock Exchange in 2021. The research sample is 294 companies. Data were analyzed using multiple regression. The results show that corporate governance positively affects social responsibility, while political connections and board of directors compensation have no effect. Investors and creditors are advised to invest in companies with good governance and disclose CSR activities. This study uses a more comprehensive index measurement.